A Phosphine-Free Approach to Primary Amides by Palladium-Catalyzed Aminocarbonylation of Aryl and Heteroaryl Iodides Using Methoxylamine Hydrochloride as an Ammonia Equivalent - Gadge, Sandip T.; Bhanage, Bhalchandra M. (Synlett, 2014)
The palladium-catalyzed synthesis of primary amides by aminocarbonylation of aryl and heteroaryl iodides under phosphine-free conditions is reported for the first time. Methoxylamine hydrochloride, acting as an ammonia equivalent, undergoes sequential carbonylation and demethoxylation under mild reaction conditions. The procedure does not require a phosphine ligand and takes place in short reaction times at low temperatures to provide the products in excellent yields.
Keywords: amides; carbonylation; palladium; catalysis; phosphine-free; cross-coupling